Implementation of Bank Indonesia Policy on the Mandatory Use of Rupiah in Indonesian Border Areas (Case Study in Sebatik Tengah Subdistrict, Nunukan Regency) - Supardi, Yusril Ihza Putra; Moh.Ikhwan Syahtaria; Yulian Azhari; Rachmat Setyawibawa; Arifuddin Uksan (Cita konsultindo, 2025)
Community encouragement to fulfill their basic needs requires border communities to find solutions to the conditions of the border areas which are still lacking. This situation requires that economic transactions in the border region tend to depend on Malaysian products, as a result of the dominance of foreign currency (ringgit) in the Central Sebatik District that cannot be avoided. Therefore, this research is titled